Pelatihan Microsoft Word Terintegrasi Mendeley dan Publish or Perish untuk Mahasiswa PKL - Nasrullah Nasrullah; Ja'faruddin Ja'faruddin (Jurnal Abdi Bangsa, 2026)
This community service activity aims to improve students' knowledge and skills in using Microsoft Word integrated with reference management tools, Mendeley and Publish or Perish, in preparation for Field Work Practice (PKL). The training was attended by 58 students from two study programs, namely Actuarial Science (26 students) and Mathematics (32 students). The implementation method used a hands-on learning approach with case studies based on academic report documents. Evaluation results showed a significant improvement in participants' abilities: 95% of participants experienced an increase in understanding of Microsoft Word advanced features, 88% successfully integrated Mendeley into their writing workflow, and 82% understood the use of Publish or Perish for literature analysis. Overall, 92% of participants stated they were better prepared to compile PKL reports professionally.